2016
DOI: 10.1111/jfb.13190
|View full text |Cite
|
Sign up to set email alerts
|

Donor life stage influences juvenile American eel Anguilla rostrata attraction to conspecific chemical cues

Abstract: The present study investigated the potential role of conspecific chemical cues in inland juvenile American eel Anguilla rostrata migrations by assessing glass eel and 1 year old elver affinities to elver washings, and elver affinity to adult yellow eel washings. In two-choice maze assays, glass eels were attracted to elver washings, but elvers were neither attracted to nor repulsed by multiple concentrations of elver washings or to yellow eel washings. These results suggest that A. rostrata responses to chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…To prepare elver washings (prepared by Galbraith et al . ()), 450 elvers (1350 g total), 90 L of well water (at 15°C), and a 25 min holding time wash were used. The concentration of the washing was 2.08 eels (6.24 g) L −1 h −1 .…”
Section: Methodssupporting
confidence: 82%
See 4 more Smart Citations
“…To prepare elver washings (prepared by Galbraith et al . ()), 450 elvers (1350 g total), 90 L of well water (at 15°C), and a 25 min holding time wash were used. The concentration of the washing was 2.08 eels (6.24 g) L −1 h −1 .…”
Section: Methodssupporting
confidence: 82%
“…Studies with European eels indicated that yellow eel odour was attractive to some juvenile stages (Briand et al, 2002;Pesaro et al, 1981;Saglio, 1982). Conversely, American eel elvers were not attracted to elver or yellow eel washings in Galbraith et al (2017), but were mildly attracted in Sorensen (1986). Therefore, these findings cannot be used to implicate attractive washing components at the present time.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations